Big data of complex networks - Dehmer, Matthias 1968-; Emmert-Streib, Frank; Pickl, Stefan 1967-; Holzinger, Andreas (Boca Raton CRC Press, Taylor & Francis Group, CRC Press is an imprint of the Taylor & Francis Group, an informa Business, 2017)
"Big Data of Complex Networks presents and explains the methods from the study of big data that can be used in analysing massive structural data sets, including both very large networks and sets of graphs. As well as applying statistical analysis techniques like sampling and bootstrapping in an interdisciplinary manner to produce novel techniques for analyzing massive amounts of data, this book also explores the possibilities offered by the special aspects such as computer memory in investigating large sets of complex networks."--Provided by publisher.
Big Data of Complex Networks: Challenges and Perspectives -- Theory and Practice of Sampling Large Networks -- Scale Graph: Large-Scale Graph Analytics Library -- Techniques for the Management and Querying of Big Data in Large Scale Communication Networks -- Fast Heuristics for Some Covering and Dominating Problems in Large-Scale Graphs -- Aspects of Large Network in Economy -- Network Visualization in the Context of Large Network Analysis.
"A Chapman & Hall book."
Includes bibliographical references and index.
Keywords: Big data; Large scale systems; System analysis